Perioperative treatment with cilostazol reverses steatosis and improves liver regeneration after major hepatectomy in a steatotic rat model - Sebastian Holländer; Maximilian von Heesen; Gereon Gäbelein; Julie Mercier; Matthias W. Laschke; Michael D. Menger; Matthias Glanemann; Antonios E. Spiliotis (Scientific Reports)
Abstract Cilostazol has previously been shown to reduce liver steatosis and enhance hepatic perfusion. We investigated the effects of cilostazol after major hepatectomy in a steatotic rat model. Six weeks prior to surgery, Sprague–Dawley rats were fed with a high-fructose diet. The treatment group received daily 5 mg/kg cilostazol. Seven days following the cilostazol treatment, all animals underwent 70% liver resection (PHX). Analysis of hepatic blood flow and microcirculation and immunohistochemical examinations were conducted 30 min after PHX (postoperative day [POD] 0) as well as on POD 1, POD 3 and POD 7. The weight of cilostazol-treated animals was significantly reduced compared to untreated controls after completion of the 6-week high-FRC diet. Furthermore, 41% macrovesicular steatosis was found in the control group compared to 8% in the cilostazol group. Hepatic arterial and portal venous perfusion were increased in the cilostazol group on POD 7. Lower liver enzyme release was found postoperatively in cilostazol-treated animals. Moreover, apoptosis and neutrophil infiltration were reduced after cilostazol treatment. Proliferation of hepatocytes and liver regeneration after PHX were significantly increased in the cilostazol group. Consequently, cilostazol should be evaluated as a novel strategy to reduce the rate of liver failure after PHX in steatotic liver.